Implementasi Pasal 22 Undang-Undang No 23 Tahun 2011 Tentang Pengelolaan Zakat di Kota Jambi - Aqilah Saufika, Zhafirah; Amin Qodri, M. (Universitas Jambi, Fakultas Hukum, 2023)
This empirical jurisprudence research is based on primary and secondary data obtained from primary sources with field research through structured interviews conducted in Jambi City, with the focus of research at KPP Pratama Jambi Telanaipura, then at the office of BAZNAS City Jambi as well as the area of Rt 24, Kel Kenali Big. Using qualitative methods presented in descriptive form, this study aims to investigate to what extent the implementation of the policy of Article 22 is specific to the City of Jambi; related to whether the policy has been fully implemented or whether there are obstacles / barriers in the effort to implement it. The results of the research show that both BAZNAS and KPP Pratama Kota Jambi have known and fulfilled the implementation of this policy by facilitating and implementing the policy in accordance with the regulations. However, the implementation of Article 22 in Jambi City is not maximum and has not been able to meet the government's expectations of reducing the double burden borne by the Muslim community equally. Evidence of the lack of Muslim taxpayers who use their zakat as a component of reducing taxable income and many of those who are still unaware of the policy as well as some other factors make why the use of such policy is still minimal in Jambi City.